Invisible Heroines. Women in the Guerrillas and Montoneras in the Central Highlands of Peru during the Wars of Independence, 1821-1824 - Valdizán Ayala, José (2026)
In recent years, Peruvian historiography has been rescuing the role of women in Peruvian history from oblivion. This has sought to move beyond a narrative that privileged, emphasized, and overvalued male roles, overlooking female participation and actions. The central objective of this research is to analyze the participation of women in the guerrilla and irregular armed groups of the central highlands of Peru during the War of Independence (1821-1824). To this end, we primarily use a series of documents published in the Documentary Collection of Peruvian Independence. Our research concludes that the role played by women in the guerrilla and irregular armed groups (as spies, combatants, and logistical support) was crucial for both the royalist and revolutionary sides.